The Importance of Social Accounting in Building Corporate Sustainability - Wahyuni; Nurul Fitri Lutfia; Febrianti Sapo; Hariyana Hermawati; Azzahra Nurwidya (JEKAMI Journal of Accounting, 2025)
In the era of globalization and intense business competition, corporate sustainability has become a critical issue involving financial, environmental, and social aspects. Social accounting plays an important role in assessing and reporting the social and environmental consequences of corporate activities, as well as helping management evaluate and communicate social performance to stakeholders. The research method applied in this study is a literature review with a qualitative approach. The steps include identifying research questions, data analysis, literature search, selection based on inclusion criteria, extraction, and evaluation. Social accounting has three main objectives: assessing the benefits and costs of a company's social contributions, ensuring social priorities are met, and providing relevant information about corporate social contributions. However, the implementation of social accounting faces internal challenges, such as a lack of awareness and limited resources, as well as external challenges, including inconsistent regulations and market pressure. Strategies to overcome these challenges include raising awareness, optimizing resources, and ensuring compliance with international standards such as GRI and ISO 26000. The integration of social accounting into business strategy involves setting sustainability objectives, developing policies and operational procedures, and conducting periodic performance monitoring and evaluation. An integrated report that includes financial, social, and environmental performance provides a comprehensive overview for stakeholders and enhances corporate accountability. Through a comprehensive and integrated approach, companies can ensure that social and environmental responsibilities become essential elements of their business plans, leading to sustainable long-term benefits for both the company and society as a whole.